2003
DOI: 10.1159/000072292
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Cranial Computed Tomography in Magnetic Resonance Imaging Era

Abstract: Objective: To evaluate the usefulness of intravenous contrast administration in cranial computed tomography (CT) in a general hospital with a magnetic resonance imaging (MRI) facility, and to establish a protocol to determine which patients would benefit most from using contrast-enhanced cranial CT. Subjects and Methods: Five hundred and forty-seven patients who underwent routine nonenhanced CT (NECT) and contrast-enhanced CT (CECT) of the brain between June 1997 and June 2001 were divided into three groups. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…3,6 Barrington et al regarded CECT as unhelpful if the NECT was normal. 7 Later studies by Chishti et al 1 and Huckman 2 demonstrated that pathology undiagnosed on NECT could subsequently be seen on CECT. Other authors suggested the use of contrast media in patients with normal NECT scans if there were focal clinical signs, 1,3,6 whilst some like Butler et al were of the opinion that a CECT on its own was as accurate as an NECT and a CECT combined.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…3,6 Barrington et al regarded CECT as unhelpful if the NECT was normal. 7 Later studies by Chishti et al 1 and Huckman 2 demonstrated that pathology undiagnosed on NECT could subsequently be seen on CECT. Other authors suggested the use of contrast media in patients with normal NECT scans if there were focal clinical signs, 1,3,6 whilst some like Butler et al were of the opinion that a CECT on its own was as accurate as an NECT and a CECT combined.…”
Section: Introductionmentioning
confidence: 99%
“…7 Later studies by Chishti et al 1 and Huckman 2 demonstrated that pathology undiagnosed on NECT could subsequently be seen on CECT. Other authors suggested the use of contrast media in patients with normal NECT scans if there were focal clinical signs, 1,3,6 whilst some like Butler et al were of the opinion that a CECT on its own was as accurate as an NECT and a CECT combined. 8 We have to consider that improved CT scanners with better resolution may mean that increased pathology would be detected on the NECT and could eliminate the need for performing a CECT of the brain.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations